Rearing Laying Hens in Aviaries Reduces Fearfulness following Transfer to Furnished Cages - Brantsæter, Margrethe; Tahamtani, Fernanda M.; Moe, Randi O.; Hansen, Tone B.; Orritt, Rachel; Nicol, Christine; Janczak, Andrew M. (Frontiers in Veterinary Science, 2016)
Appropriate rearing is essential for ensuring the welfare and productivity of laying hens. Early experience has the potential to affect the development of fearfulness. This study tested whether rearing in aviaries, as opposed to cages, reduces the fearfulness of laying hens after transfer to furnished cages. Fear responses were recorded as avoidance of a novel object in the home cage. Lohmann Selected Leghorns were reared in an aviary system or conventional rearing cages and then transported to furnished cages at 16 weeks, before the onset of lay. Observations of a selection of birds were conducted at 19 (N = 50) and 21 (N = 48) weeks of age selected from 50 and 48 independent cages. At 19 and 21 weeks, cage-reared birds showed higher levels of fearfulness indicated by spending more time away from the novel object compared to aviary-reared birds. These results suggest that rearing in an enriched aviary environment reduces fearfulness up to the fifth week after transfer to a new housing system, compared to rearing in cages.